Pertumbuhan dan Sintasan Ikan Nila (Oreochromis niloticus) yang diberi Kombinasi Pakan Buatan Dari Tepung Cacing Tanah (Pheretima sp.) dan Alga Coklat (Sargassum spp.) - Tri Rima Setyawati, Hilyadi Edstiv Bagayo, Junardi, (Jurnal Protobiont, 2019)
The potential for freshwater aquaculture in West Kalimantan is still high, including one of them is the Nile tilapia (Oreochromis niloticus). The purpose of this study was to determine the optimal growth and best survival rateÂ by a combination of Fish, Earthworm Pheretima sp. and Brown seaweed Sargassum spp flour. The method used is Completely Randomized Design with four treatments and five replications. The result showed that treatments with > 60% plant raw materials shows the best resulting not only growth but also survival rate. Feed with a combination of these raw materials showedÂ an allometric positive growth pattern.